Recovery of fenbendazole efficacy on resistant Haemonchus contortus by management of parasite refugia and population replacement - Muchiut, Sebastian; Fernandez, Alicia Silvina; Lloberas, María Mercedes; Steffan, Pedro Eduard; Luque, Sonia; Cardozo, Patricia Alejandra; Bernat, Gisele Anahí; Riva, Eliana; Fiel, César Alberto (Elsevier, 2021)
The recovery of fenbendazole efficacy against Haemonchus contortus was attempted in a sheep intensive production system, using a strategy of population replacement in which the initial absolute efficacy of fenbendazole was 0%. The strategy was based on managing the parasite populations in refugia. Firstly, the resistant parasite population was reduced by means of anthelmintic treatments with efficacious drugs (Phase I), then a new, susceptible population was introduced in summer by way of artificially infected lambs at weaning, which were left to graze on the experimental pasture for eleven months (Phase II). Lastly, the impact of the replacement strategy, in terms of benzimidazole efficacy, was measured (Phase III). Faecal egg counts from permanent lambs and worm burdens as a measure of pasture infectivity from tracer lambs were determined throughout the study. During Phase I, faecal egg counts diminished from a peak of 2968 (300–7740) epg to 0 epg at the end, while adult worm burdens of H. contortus were reduced from 2625 (800–5100) to 0, which showed that the treatment strategy used in Phase I was effective in reducing the resistant population. These parameters also showed that good levels of pasture contamination and infectivity were achieved in Phase II, as faecal egg counts of up to 7275 (3240–13080) epg and adult worm burdens of 500 (200–800) H. contortus were reached. The absolute benzimidazole efficacy on H. contortus estimated at 16 months post-population replacement (Phase III) was 97.58%. The results lead to the conclusion that the recovery of anthelmintic efficacy of fenbendazole against a resistant population of H. contortus may be achieved by means of a strategy based on management of refugia and a subsequent introduction of a susceptible population. This strategy might be translatable to other resistant nematode genera.